A glimpse of otherness: New directions for democratization in Mexico - Makowski Muchnik, Sara (1997)
Traveling through the depths of Mexico's history, any traveler, expert or inexperienced, encounters varied faces and figures. The faces of otherness have been transformed over the centuries, but the material with which they are made has not been very different. Historical events, ideological visions and ways of discovering and relating have differentially modeled the complex fragments of otherness deposited in that kaleidoscope discovered by Columbus.